The Implementation of Merdeka Belajar Curriculum in Islamic Education Learning to Develop Students' Independent Character - Syafi'i, Syafi'i; Ali, Mukti; Lubid, Adlan Fauzi (International Journal of Educational Sciences and Development, 2025)
Purpose – This study aims to examine the implementation of the Merdeka Belajar Curriculum in Islamic Education (PAI) learning, covering the aspects of planning, implementation, and evaluation, as well as how this curriculum contributes to shaping students' independent character at SMP Sumpah Pemuda Jakarta Barat. Methodology/approach –The research employs a qualitative method with a descriptive approach. Triangulation techniques are applied to ensure the validity of data collected through in-depth interviews with the School Principal, Vice Principal for Curriculum Affairs, PAI teachers, and student representatives, as well as direct classroom observations . Findings – The research findings indicate that the planning of the Merdeka Belajar Curriculum is carried out collaboratively between the school administration and PAI teachers, although challenges remain in understanding the new curriculum. In its implementation, learning focuses more on practical activities rather than theoretical lessons, such as memorizing Quranic verses, which has proven effective in fostering students’ independence. Meanwhile, the evaluation process is conducted holistically, combining written tests, oral assessments, and practical worship evaluations, all of which contribute to strengthening students' independent character. Novelty/value – This study provides new insights by demonstrating that the implementation of the Merdeka Belajar Curriculum in PAI learning has a positive impact on developing students' independent character. However, challenges remain, particularly in teachers' and schools' understanding of the new curriculum. The uniqueness of this research lies in its holistic evaluation approach and its focus on student independence within the context of religious education.